Bioclaustration trace fossils in epeiric shallow marine stromatolites: the Cretaceous‐Palaeogene Yacoraite Formation, Northwestern Argentina. (29th November 2013) - Cónsole‐Gonella, Carlos; Marquillas, Rosa A.
<x xml:space="preserve">Abstract</x> The shallow carbonate facies at the top of the Yacoraite Formation (Late Cretaceous–Early Palaeocene) in the Metán sub‐basin, Salta Basin (Cretaceous‐Eocene), northern Argentina, have domal stromatolitic boundstones with peculiar cavities, interpreted here as bioclaustrations. The cavities appear to have been produced by organisms that lived within the microbial mat contemporarily with its growth, producing a distinctive ichnofabric. This is the oldest reported record of bioclaustrations in stromatolites, and the first in shallow marine environments. The interpretation of the facies suggests a stressed shallow, restricted setting with variations in salinity, represented by an intertidal environment with an extensive tidal flat. Bioclaustrations, stromatolites, endobiont Yacoraite Formation (Cretaceous‐Palaeogene), Northwestern Argentina.